Governing Uranium in Canada - Cindy Vestergaard (Danish Institute for International Studies (DIIS), 2015)
Canada has been a long-time key producer and global supplier of uranium. It has produced more uranium than any other country, close to 500,000 tU since 1942. It also hosts the worlds largest operating mine (in terms of annual production), mill and refinery and is home to the worlds largest high-grade uranium deposits. Given its high concentrations, Canada is the only producer that has to "water down" its rock. Over seven decades, Canadas production of uranium has evolved from being dedicated to fulfilling military contracts in the 1940s and 1950s to being focused on the environment, non-proliferation and safety. Initially a state secret, uranium mining and trade have become transparent with a public hearing-based licensing process, regulatory oversight and annual reporting of operational safety and environmental performance. This level of transparency and regulation is unparalled by any other industry in Canada, forming the basis of Canadas reputation as a solid and steady supplier. This study analyses the Canadian uranium supply industry, the evolution of its development, and the legal framework that regulates uranium production and trade in Canada. It is part of the larger Governing Uranium project led by the Danish Institute for International Studies (DIIS), which explores the dimensions of security of natural uranium in a changing global market.
Keywords: 300